Induction Motor Drives Speed Control Using Digital Signal Controllers (DSC) - Susila, M.; Karthik , B.; Virgin, G. Angelo (International Journal of Psychosocial Rehabilitation, 2018)
Induction motor is widely used in large scale industries as much as employed in small scale industries. In industrial employment, the three phase induction motor faces numerous drawback when they are subjected to heavy loads. These exerted forces are related as disturbances in motor resulting in classification namely internal and external disturbances. Induction motor may exhibit both disturbances under critical conditions; to eliminate these disturbances a microcontroller is employed. This microcontroller can work with all capabilities that a digital signal processor can do. The dsPIC microcontrollerisa16-bit microcontroller unit ((MCU) with computation and throughput capabilities of DSP processor in single core. The digital signal controllers are coded with the vector control r field oriented control scheme to control the speed of the three phase induction motor. A driver circuit of closed loop IGBT is used to limit the fluctuations of current in the induction motor.